Developing science magazine integrated with contextual teaching and learning approach based on local potential in talang siring beach, Indonesia - Fikriyah, Aida; Ahied, Mochammad; Qomaria, Nur (Biosfer: Jurnal Pendidikan Biologi, 2024)
One of exciting learning media is magazine in which students prefer to read this rather than books since magazine contains of various colorful images and appropriate information. Magazine can be developed by integrating with science learning approach in order that students can comprehend the concepts easier. This study aims at developing science magazine which is integrated with contextual teaching and learning approach according to the study findings in Talang Siring. The research included in a research and development study, using Borg and Gall model. The research was conducted on October to November 2022, which is located in Talang Siring Pamekasan, Indonesia by identifying ecosystem of beach and mangrove. Furthermore, the observation findings were arranged systematically in developing science magazine. Science magazine was evaluated by experts in concept and learning media. Findings indicated that the science magazine is valid with media validity score 93.5 and content validity score 91.6. Therefore, it is appropriate to implemented in science learning. Therefore, it can be concluded that science magazine is able to be used as learning media in science learning process